Octadentate oxine-armed bispidine ligand for radiopharmaceutical chemistry - Choudhary, Neha; Dimmling, Alexander; Wang, Xiaozhu; Southcott, Lily; Radchenko, Valery; Patrick, Brian O.; Comba, Peter; Orvig, Chris (Inorganic chemistry, 2019)
In this study, we present the synthesis and characterization of the octadentate bispidine ligand, H2bispox2 and its complexes with medicinally useful radiometal nuclides (111In3+ and 177Lu3+), including their X-ray diffraction single crystal structures with the stable isotopes. 111InCl3 radiolabels the ligand quantitatively at ambient conditions ([L] = 10-5 M, room temperature, pH 7 and 15 min) and the in vitro human serum stability assays demonstrated high stability of the [111In(bispox2)]+ complex over 5 days. Moreover, the β- emitter 177Lu radiolabels the ligand at 37 °C in 30 min (pH 8). These initial investigations reveal the potential of the octadentate bispidine ligand H2bispox2 as a useful chelator for 111In and 177Lu-based radiopharmaceuticals.
Gesehen am 10.10.2019